(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to test the impact of financial inclusion on economic growth in Syria during the period from 2003 to 2017, using annual data. We measured the financial inclusion by the growth of number of branches of commercial banks and insurance companies, as indicators of individual’s access to the financial services. and growth of volume of loans and deposits with commercial banks as indicators of individual’s using of the financial services; and the economic growth was measured by real GDP growth. To achieve the objective of this study, we first tested the stability of time series of the selected variables, and then we tested the long-term relationship between explanatory variables and the dependent variable using ARDL. The results showed that both of the volume of loans and deposits with commercial banks positively affect on the economic growth, and the number of insurance companies has a positive but non-significant effect on economic growth, and the number of branches of commercial banks has a negative but also non-significant effect on economic growth in Syria during the study period.